Sternberg Thinking Skills Levels for Vocational College Students and Analysing Demographic Disparities - Mei Heong, Yee (Online Journal for TVET Practitioners, 2024)
Sternberg’s Thinking Skills are essential in an effort to assist students in was conducted to identify the level of Sternberg thinking skills based on vocational college student with students demographic. The design of this study was quantitative perception approach. A total of 193 students of Likas vocational college and Miri Vocational College were randomly selected as the study samples. A questionnaire, administered through ’Google Forms,’ served as the research instrument for data collection. The gathered data were subsequently analyzed using SPSS software. The study focused on the analytical, creative, and practical dimensions. The findings indicate that a majority of students perceive themselves to have a high level of Sternberg thinking skills. Overall, the study suggests that students have a mastery of Sternberg thinking skills, enabling them to actively regulate cognitive processes and possess cognitive knowledge in problem-solving methods, thereby achieving better learning goals. In summarizing the findings of this study, it was observed that the level of Sternberg’s thinking skills, as perceived by vocational college students, is high across all elementts, including analytical, practical, and creative dimensions. Regarding demographic factors, significant differences were identified in terms of gender, field of study, and academic achievement among students. This indicates that technical students are well-equipped to apply Sternberg Thinking Skills in the teaching and learning process. The insights gained from the study results hold significant importance for educators, enabling them to gain a deeper understanding of students and choose appropriate teaching approaches to facilitate effective learning processes. Undoubtedly, educators play a crucial role in determining the success of students, particularly in mastering Sternberg thinking and problem-solving skills.